Investment of Self-Confidence in Cingkrik Rawa Belong Pencak Silat for Elementary School Students - Sa'odah Sa'odah; Mamat Supriatna (Al-Adzka: Jurnal Ilmiah Pendidikan Guru Madrasah Ibtidaiyah, 2021)
This article aims to describe thoroughly the value of self-confidence in Pencak Silat activities for elementary school students. The scope includes the value of self-confidence in Pencak Silat Cingkrik Rawa Belong. The research method used is a literature review and field visits that include observation and interviews. The research subjects were the head of the Lengkong Arts and Culture House Foundation and the research object was elementary school students who were active in Pencak Silat activities in elementary schools. The research sites are the Cingkrik Rawa Belong Lengkong Cultural Art House and the Primary School in Tangerang. The instruments used were interviews and observation. The result of this research is that the value of self-confidence in Pencak Silat activities is the value obtained by children from training or Pencak silat activities and then retrained through the experience of the championships that have been followed The use-value contained in the Cingkrik Pencak Silat activity can be used as learning to instill confidence in elementary school students.